Dose and timing of injections for effective cyclosporine A pretreatment before renal ischemia reperfusion in mice. - Sandrine Lemoine; Bruno Pillot; Lionel Augeul; Maud Rabeyrin; Annie Varennes; Gabrielle Normand; Delphine Baetz; Michel Ovize; Laurent Juillard (PLoS ONE)
Background There is experimental evidence that lethal ischemia-reperfusion injury (IRI) is largely due to mitochondrial permeability transition pore (mPTP) opening, which can be prevented by cyclosporine A (CsA). The aim of our study is to show that a higher dose of CsA (10 mg/kg) injected just before ischemia or a lower dose of CsA (3 mg/kg) injected further in advance of ischemia (1 h) protects the kidneys and improves mitochondrial function. Methods All mice underwent a right unilateral nephrectomy followed by 30 min clamping of the left renal artery. Mice in the control group did not receive any pharmacological treatment. Mice in the three groups treated by CsA were injected at different times and with different doses, namely 3 mg/kg 1 h or 10 min before ischemia or 10 mg/kg 10 min before ischemia. After 24 h of reperfusion, the plasma creatinine level were measured, the histological score was assessed and mitochondria were isolated to calculate the calcium retention capacity (CRC) and level of oxidative phosphorylation. Results Mortality and renal function was significantly higher in the CsA 10 mg/kg-10 min and CsA 3mg/kg-1 h groups than in the CsA 3mg/kg-10 min group. Likewise, the CRC was significantly higher in the former two groups than in the latter, suggesting that the improved renal function was due to a longer delay in the opening of the mPTP. Oxidative phosphorylation levels were also higher 24 h after reperfusion in the protected groups. Conclusions Our results suggest that the protection afforded by CsA is likely limited by its availability. The dose and timing of the injections are therefore crucial to ensure that the treatment is effective, but these findings may prove challenging to apply in practice.